Analisis Conducting Simfoni Beethoven No. 5 Conductor Indonesia - Pipin Garibaldi (EKSPRESI, 2009)
The Analysis on Conducting Beethoven Sympony No. 5 Done By Indonesian Conductor. This paper discusses the weaknesses of Indonesian music conductors with Javanese cultural background Indonesian conductors need to understand the characteristics of the Western and Eastern culture that deal with thinking patterns, customs, and attitudes. Beethoven No. 5 is loud, serious, dramatic, and heartrending. To be able to perform those expressions, good conducting techniques and analysis on the composition are needed. Keywords: Conducting, music conductor, performing arts.